Exploring material flow in friction stir welding: Tool eccentricity and formation of banded structures - Gratecap, F.; Girard, M.; Marya, S.; Racineux, G. (International journal of material forming, 2012)
Surface striations with spacing equal to feed rate per rotation and banded structures in the weld nugget are some of the striking features of friction stir welding. However, their formation is still subject to some debate. This study contributes to comprehend their formation by evaluating the possible role played by the eccentricity of the tool during the welding of an aluminium alloy and using a plasticine as its analogue. The eccentric movement is visualized to generate both surface and bulk striations in plasticine. By voluntarily using non optimized welding conditions on aluminium, the material flow has been deduced and confronted with direct visual observations through high speed camera on plasticine. In the non closed section of the weld, two lobes each with thickness equal to feed rate per rotation were observed. First lobe corresponds to flow induced by the pin and tests on plasticine showed constant volume displacement per rotation for a given tool eccentricity. The second lobe is generated by material flow from under the shoulder back to the rear of the pin. The assembling or not of these two lobs behind the pin can explain some of the characteristic patterns observed in the weld nugget such as onion rings, oxide dispersions and cavities.